Phosphodiesterase (PDE) 5 inhibitors sildenafil, tadalafil and vardenafil impact cAMP-specific PDE8 isoforms-linked second messengers and steroid production in a mouse Leydig tumor cell line. (15th February 2022) - Limoncella, Silvia; Lazzaretti, Clara; Paradiso, Elia; D'Alessandro, Sara; Barbagallo, Federica; Pacifico, Salvatore; Guerrini, Remo; Tagliavini, Simonetta; Trenti, Tommaso; Santi, Daniele; Simoni, Manuela; Sola, Marco; et al.
Abstract: Type 5 phosphodiesterase (PDE5) blockade by inhibitors (PDE5i) results in intracellular cyclic guanosine monophosphate (cGMP) increase and smooth muscle relaxation and are used for the treatment of men erectile dysfunction. Although they have high specificity for PDE5, these inhibitors are suspected to cross-interact also with cyclic adenosine monophosphate (cAMP)-specific PDEs, inducing the intracellular accumulation of this cyclic nucleotide and related testosterone increase, positively impacting male reproductive parameters. However, the link between the use of PDE5i and the activation of cAMP-mediated steroidogenesis is still unclear. We have investigated whether three PDE5i, sildenafil, tadalafil and vardenafil, cross-interacts with the high affinity cAMP-specific enzymes type 8A and 8B PDEs (PDE8A and PDE8B), in live, transfected mouse Leydig tumor (mLTC1) and human embryonic kidney (HEK293) cell lines in vitro . The PDE5i-induced production of cAMP-dependent testosterone and its precursor progesterone was evaluated as well. We have developed PDE8A/B biosensors and modified cyclic nucleotides confirming enzyme binding to cAMP, but not to cGMP, in our cell models. cAMP binding to PDE8A/B was displaced upon cell treatment with PDE5i, revealing that sildenafil, tadalafil and vardenafil have similar effectiveness in live cells, in vitro . The cross-interaction between PDE5i and PDE8A/B supports the gonadotropin-enhanced intracellular cAMP increase, occurring together with cGMP increase, as well as steroid synthesis. Indeed, we found that Leydig cell treatment by PDE5i increases progesterone and testosterone production triggered by gonadotropins. We demonstrated that PDE5i may interact with the cAMP-specific PDE8A and PDE8B, possibly inducing intracellular cAMP and sex steroid hormone increase. These findings support clinical data suggesting that PDE5i might increase testosterone levels in men. Highlights: Phosphodiesterase 5 inhibitors (PDE5i) may cross-interact with cAMP-specific PDEs. Sildenafil, tadalafil and vardenafil interact with PDE8A and B in Leydig cells. PDE8A/B inhibition by PDE5i increases cAMP and sex steroid hormones. These data suggest a PDE8 mediated testosterone increase in a Leydig cell line upon PDE5i.